Wolfenbüttel HAB Cod. Guelf. 51. 9. Aug. 4º and BL, Harley MS. 3542: Complementary Witnesses to Ralph Hoby's 1437 Treatise on Astronomical Medicine. (2008) - Voigts, Linda Ehrsam
No abstract available